(untitled) (Journal of the College of Basic Education, 2022)
Whereas observing God Almighty for His servants was highest level of faith , Its wording occupied multiple places in the Holy Qur’an , so this research came to study these words as a semantic grammatical study , and It was based on an introdction and two studies . for the nominative observati words , but the second one deals with actual verbal words .I have benefited from multiple sources and references in carrying out this research , including books on the sciences of the Qur’an and its interpretation grammar books , as well as linguistic dictionaries